Clinical study of abnormal glucose metabolism screening for acute ischemic cerebral apoplexy in patients - Wen-Zhen He; Xian-Guang Chen; Wen-Jie Chen; Xiao-Ling Xu (Wolters Kluwer Medknow Publications, 2015)
Ischemic stroke refers to a focal neurological deficit attributable to the conditions created by the occlusion of an intracranial artery. We investigated how screening for abnormal glucose metabolism in acute ischemic cerebral apoplexy inpatients might be used to develop a more reasonable treatment plan and improve the prognosis of patients with acute ischemic stroke. A total of 686 patients with acute ischemic stroke, hospitalized from January 2007 to December 2010 in the neurological department of the first affiliated hospital in China Shantou Medical College, was examined in this study. We recorded each patient's sex, age, smoking history, height, weight, blood pressure, waist circumference, random blood glucose, and fasting blood glucose, also noting if the patient had a record of having high blood sugar. In addition, we conducted a 75 g oral glucose tolerance test (OGTT) for undiagnosed diabetes patients in order to determine the status of glucose metabolism. We find that there were 368 (66.1%) cases of hospitalized cerebral vascular disease patients with abnormal glucose metabolism of which 185 (33.2%) cases are diabetes, and 183 cases (32.9%) are with impaired glucose regulation, and 189 cases (33.9%) are with normal glucose tolerance. Totally, 130 cases had been diagnosed as diabetes before their admission, accounting for 23.3% of all patients. Totally, 427 patients are without diabetes history, however, 29 diabetes cases (accounting for 15.7% of all diabetic patients) were found after a non-OGTT. We concluded that patients with acute ischemic stroke are often associated with abnormal glucose metabolism, and so OGTT screening tests will help doctors to recognize acute ischemic stroke patients.